2001
DOI: 10.1074/jbc.m009963200
|View full text |Cite
|
Sign up to set email alerts
|

Differential MAPK Pathways Utilized for HGF- and EGF-dependent Renal Epithelial Morphogenesis

Abstract: Cells derived from the inner medullary collecting duct undergo in vitro branching tubulogenesis to both the c-met receptor ligand hepatocyte growth factor (HGF) as well as epidermal growth factor (EGF) receptor ligands. In contrast, many other cultured renal epithelial cells respond in this manner only to HGF, suggesting that these two receptors may use independent signaling pathways during morphogenesis. We have therefore compared the signaling pathways for mIMCD-3 cell morphogenesis in response to EGF and HG… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

8
78
1

Year Published

2002
2002
2016
2016

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 93 publications
(87 citation statements)
references
References 41 publications
8
78
1
Order By: Relevance
“…Our recent determination that HGF-stimulated epithelial cell morphogenesis requires ERK1/2 activation provides a potential physiologic role for ERK-regulated PI3K activation (18). Interestingly, in this same study, we found that EGF, but not HGF, activates ERK5 in addition to ERK1/2.…”
supporting
confidence: 65%
See 2 more Smart Citations
“…Our recent determination that HGF-stimulated epithelial cell morphogenesis requires ERK1/2 activation provides a potential physiologic role for ERK-regulated PI3K activation (18). Interestingly, in this same study, we found that EGF, but not HGF, activates ERK5 in addition to ERK1/2.…”
supporting
confidence: 65%
“…U0126 has been shown to inhibit MEK1, MEK 2 (20), and MEK5 (18) at concentrations less than 50 M, but it does not inhibit MEK3, MEK4, MEK6, MEK7, protein kinase C␣, protein kinase A, PDK1, or other tested serine/threonine kinases (20). U0126 was used rather than PD98059, because we have found that EGF-mediated ERK5 activation, which is critical for EGF-mediated mIMCD-3 cell morphogenesis, is fully inhibited by U0126 but only partially inhibited by PD98059 at concentrations Յ100 M (18). Following EGF stimulation, cells were lysed in 800 l of ice-cold radioimmune precipitation lysis buffer containing 50 mM Tris, pH 7.5, 150 mM NaCl, 1 mM EDTA, 1% Triton X-100, 1% sodium deoxycholate, 0.1% SDS, 2 g/ml aprotinin, 2 g/ml leupeptin, 2 g/ml pepstatin A, 10 mM NaF, 1 mM phenylmethylsulfonyl fluoride, and 1 mM Na 3 VO 4 .…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Ngal Stimulates Transient ERK Activation-We have demonstrated previously that cell migration and branching morphogenesis stimulated by HGF and EGF require the activation of the MAPK pathway (5,26). The ability of Ngal to activate MAPK was therefore examined in cells stimulated with Ngal as compared with HGF.…”
Section: Resultsmentioning
confidence: 99%
“…Akt activation is downregulated in confluent cells. Previous studies in our laboratory and others have shown that HGFstimulated cell migration requires activation of several intracellular signaling pathways, including the PI 3-K and MAPK pathways (9,15,19). HGF-stimulated activation of the downstream proteins Akt (for the PI 3-K pathway) and ERK (for the MAPK pathway) was therefore examined under nonconfluent and confluent conditions using activation state-specific antibodies.…”
Section: Resultsmentioning
confidence: 99%